Ontological Approach to the Problem of Consciousness - Alimatova Nargis Abdukhalilovna (Indonesian Journal Publisher, 2026)
This article provides a theoretical examination of the problem of consciousness as one of the central issues in modern philosophy, with particular attention to its relation to the functioning of the human mind and brain. The study aims to analyze consciousness as a fundamental category of ontology and to trace the major philosophical approaches to this problem throughout the history of philosophical thought. Special emphasis is placed on recent conceptions of consciousness developed within contemporary Western philosophy. Furthermore, the article identifies current trends in the investigation of the nature of the human mind and evaluates their philosophical significance. The findings of the study contribute to a deeper understanding of the ontological, epistemological, and interdisciplinary dimensions of consciousness research.